Azobenzenesulfonamide Carbonic Anhydrase Inhibitors as New Weapons to Fight Helicobacter pylori: Synthesis, Bioactivity Evaluation, In Vivo Toxicity, and Computational Studies - Letizia Giampietro; Beatrice Marinacci; Alice Della Valle; Ilaria D'Agostino; Aldo Lauro; Mattia Mori; Simone Carradori; Alessandra Ammazzalorso; Barbara De Filippis; Cristina Maccallini; Andrea Angeli; Clemente Capasso; et al. (MDPI AG, 2024)
Research into novel anti-Helicobacter pylori agents represents an important approach for the identification of new treatments for chronic gastritis and peptic ulcers, which are associated with a high risk of developing gastric carcinoma. In this respect, two series of azobenzenesulfonamides were designed, synthesized, and tested against a large panel of human and bacterial CAs to evaluate their inhibitory activity. In addition, computational studies of the novel primary benzenesulfonamides (4a-j) were performed to predict the putative binding mode to both HpCAs. Then, the antimicrobial activity versus H. pylori of the two series was also studied. The best-in-class compounds were found to be 4c and 4e among the primary azobenzenesulfonamides and 5c and 5f belonging to the secondary azobenzenesulfonamides series, showing themselves to exert a promising anti-H. pylori activity, with MIC values of 4-8 μg/mL and MBCs between 4 and 16 μg/mL. Moreover, the evaluation of their toxicity on a G. mellonella larva in vivo model indicated a safe profile for 4c,e and 5c,f. The collected results warrant considering these azobenzenesulfonamides as an interesting starting point for the development of a new class of anti-H. pylori agents.